Genetic variation in statin intolerance and a possible protective role for UGT1A1. (January 2018) - V Willrich, Maria Alice; Kaleta, Erin J; Bryant, Sandra C; Spears, Grant M; Train, Laura J; Peterson, Sandra E; Lennon, Vanda A; Kopecky, Stephen L; Baudhuin, Linnea M
The etiology of statin intolerance is hypothesized to be due to genetic variants that impact statin disposition and clearance. We sought to determine whether genetic variants were associated to statin intolerance. The studied cohort consisted of hyperlipidemic participants (n = 90) clinically diagnosed with statin intolerance by a cardiologist and matched controls without statin intolerance. Creatine kinase activity, lipid profiles and genetic analyses were performed on genes involved in statin metabolism and included UGT1A1 and UGT1A3 sequencing and targeted analyses of CYP3A4*22, CYP3A5*3, SLCO1B1*5 and *1b, ABCB1 c.3435C>T, ABCG2 c.421C>A and GATM rs9806699. Although lipids were higher in cases, genetic variant minor allele frequencies were similar between cases and controls, except for UGT1A1*28, which was less prevalent in cases than controls.